Enhancing Students’ Creativity In Food Processing Through The Implementation Of P5ra Mentoring At Min 1 Labuhanbatu - Wina Handayani Br Batubara; Ika Sundari; Zulhimma (Lembaga Riset Ilmiah, 2025)
This Community Service Program (PKM) conducted at MIN 1 Labuhanbatu aims to enhance teachers’ competency in implementing the Independent Curriculum (Kurikulum Merdeka) and to foster students’ creativity and skills through the Pancasila Student Profile and Rahmatan lil ‘Alamin Project (P5RA). The program began with a four-day training series covering curriculum policy updates, the development of the Madrasah Operational Curriculum (KOM), module and assessment design, and project planning for P5RA. The subsequent phase involved mentoring students in a local food-processing project, specifically producing rengginang pulut (glutinous rice crackers) by Grade 5A students. The results indicate improved teacher capability in designing and implementing project-based learning aligned with the Independent Curriculum. Students also demonstrated increased creativity, collaboration, and technical proficiency through hands-on food processing stages, including material preparation, mixing, steaming, shaping, drying, and packaging. Furthermore, the project fostered entrepreneurial values as the final product was marketed at the school canteen in both raw and ready-to-eat packaging.